Design and Implementation of a Documentation Tool for interactive Commandline Sessions - Dewald, Andreas; Freiling, Felix; Weber, Tim (Sixth International Conference on IT Security Incident Management and IT Forensics, 2011)
In digital investigations it is important to document the examination of a computer system with as much detail as possible. Allthough never designed for digital investigations, many experts use the software script to record their whole terminal session while analyzing a target system. We analyze script's deficiencies and present the design and implementation of for script (forensic script), a software providing additional capabilities and mechanisms for digital investigations, following the paradigm of literate programming. © 2011 IEEE.
UnivIS-Import:2015-04-20:Pub.2011.tech.IMMD.lehrst.design